Idle No More: identité autochtone actuelle, solidarité et justice sociale : Entrevue avec Melissa Mollen Dupuis et Widia Larivière - Gentelet, Karine (Nouvelles pratiques sociales, 2014)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; environnement; féminisme autochtone; militance; pol4105; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; science politique et droit; thématiques

Praticing indigenous feminism: Resistance to Imperialism - Stewart-Harawira, Makere (Making space for aboriginal feminism, 2007)
This chapter is situated within the complexities of the new forms of imperialism that characterize a world seemingly gone mad. The conviction that both the project of decolonization and that of human survival and ultimately, peace for a world hovering on the brink of self-destruction require, at the very least, the return of the feminine principle and in the process, right balance and the compassionate mind, to the center of our political ontologies, is central to this chapter. The thesis is two-fold: firstly, that Indigenous women have a vital role to play in the realization of alternative models of “being in the world‟ and secondly, that this represent a particularly poignant paradox.
Keywords: OFDIG; approches et analyses; discipline; femmes*; féminisme autochtone; impérialisme; militance; ressource en ligne; science politique; science politique et droit; sofia; thématiques